2012
DOI: 10.1590/s1413-81232012001000020
|View full text |Cite
|
Sign up to set email alerts
|

Judicialização do acesso ao tratamento de doenças genéticas raras: a doença de Fabry no Rio Grande do Sul

Abstract: Judicialização do acesso ao tratamento de doenças genéticas raras: a doença de Fabry no Rio Grande do Sul

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0
13

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 18 publications
0
14
0
13
Order By: Relevance
“…The first year of the publications included in the review was 2005, and there was a peak in the years 2010 and 2011. The data refer to studies done in the states of Pernambuco 5 , Rio Grande do Sul 2,6 , Minas Gerais 7,8 , Rio de Janeiro 9,10,11,12 , and São Paulo 13,14,15,16,17 , besides one article that collected data directly from the Ministry of Health in Brasilia 18 . The studies that examined the most lawsuits (between 2,000 and 2,927 cases) were done in the states of São Paulo, Rio de Janeiro, and Santa Catarina 7,12,14,16,19 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The first year of the publications included in the review was 2005, and there was a peak in the years 2010 and 2011. The data refer to studies done in the states of Pernambuco 5 , Rio Grande do Sul 2,6 , Minas Gerais 7,8 , Rio de Janeiro 9,10,11,12 , and São Paulo 13,14,15,16,17 , besides one article that collected data directly from the Ministry of Health in Brasilia 18 . The studies that examined the most lawsuits (between 2,000 and 2,927 cases) were done in the states of São Paulo, Rio de Janeiro, and Santa Catarina 7,12,14,16,19 .…”
Section: Resultsmentioning
confidence: 99%
“…Six studies 2,9,10,11,14,17 reported a predominance of public legal representation (Office of the Public Defender, Office of the Public Prosecutor, Offices of Municipal, State, and Federal Attorneys). In five studies 6,7,8,16,20 , most plaintiffs were represented by private attorneys. In one study, free legal aid was provided to all the plaintiffs 6 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations